The Role of the “EcoMasjid” Program in Jakarta in the Development of Awareness of Eco-Friendly Living Culture - Purwanto, Heru; Imawan, Ficky Augusta; Reynold, Wiliam (Cities and Urban Development Journal, 2024)
Background: The acceleration of the social and economic today has produced a new phenomenon and challenge: Environmental crisis. As a result, various studies from diverse disciplines and perspectives, seek to carry out various mitigative and preventive analyses and innovations. One of them is through a religious approach that is believed to influence the movement, especially in the context of Indonesia with a Muslim population of 240.62 million as the majority population in Indonesia and a total of 299,692 mosques. Aims: This study seeks to study the role of one of the efforts made by the Indonesian Ulema Council (MUI) in the "EcoMasjid" program as an effort to move mosques which are considered not only religious spaces, but community spaces, and the epicenter of social growth. Methods: Through a qualitative approach in the form of interview, observation, and literature study methods, the author uses several supporting concepts such as EcoMosque, Religious Creativity, and the Relationship between Religious Organizations and the social patterns of the community in social issues. Results: The results of this study show that EcoMasjid as a program, in general, has an impact on improving the culture of environmentally friendly living. This is supported by several efforts such as infrastructure approaches, lectures related to environmental issues, and other communication with pilgrims. Conclusion: This program still needs expansion in the context of participation, as well as the involvement of young people to bring innovations for the development of EcoMasjid in building closeness and relevance in the community.